Implementation of Contemporary Architecture in the Shape of the Main Building in the Central Area of the Creative Arts and Music Industry in Surabaya - Stevanus Agustian Wibowo; Ika Ratniarsih; Failasuf Herman Hendra (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
The main building of the Creative Arts Music Industry Center in Surabaya has a function to facilitate the growth and development of the creative arts music industry in Surabaya. Among them are Pop, Rock, Dangdut, Jazz, Classical, and Traditional Music. The facilities in this building include indoor music performances, a music library, music education, music production, music recording, and a music collaborator. The main building is designed with the application of a contemporary architectural theme. Contemporary architecture is architecture that has the freedom to express itself and has the desire to create a new and different work from previously existing architectural works. So that it can produce an appearance that is beyond the ordinary; their appearance gives an attractive, exploratory and complex impression. In its application, the form of this main building adopts a form that is quite closely related to the art of music, namely the form of a grand piano musical instrument. With this building form, it is expected to bring up a concept of contemporary architecture through a new form that has never existed before and is able to express the activities carried out in the main building.